Bio-Diesel Plant Millettia pinnata (L.) Panigrahi Goes down the Priority List of Foresters and Landscapers for Planting Due to Severe and Persistent Attack of Blotch Leaf Miner, Acrocercops anthracurieus (Meyrick) - Chander, Jagdish (Indian Forester, 2018)
No Abstract.